Plastiken und Skulpturen - Riedl, Peter Anselm (Abcverl., 2008)
Sigrid und Viktor Dulger sind die Förderer
Keywords: Goertz, Jürgen -- 1939-; Matschinsky-Denninghoff, Martin -- 1921-2020; Akiyama, Hiromi -- 1937-2012; Pokorny, Werner -- 1949-2022; Heidelberg; Bildband; Akiyama, Hiromi; Goertz, Jürgen; Wesendonck, Otto; Pokorny, Werner; Matschinsky-Denninghoff, Martin; Matschinsky-Denninghoff, Brigitte; Geschichte 1985-2007; Öffentlicher Raum; Stahlplastik